2019
DOI: 10.1155/2019/5904903
|View full text |Cite
|
Sign up to set email alerts
|

Vergence and Accommodative Dysfunctions in Emmetropic and Myopic Chinese Young Adults

Abstract: Purpose. To investigate the association between refractive error and common binocular vision and accommodative dysfunctions in Chinese adults and to report the percentage of these disorders in this sample population. Methods. This was a single-site, prospective cross-sectional clinic-based study. A total of 415 Chinese participants aged between 21 and 38 years were grouped into 4 refractive error groups (emmetropia, low, moderate, and high myopia) based on the spherical equivalent power of noncycloplegic refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 19 publications
5
46
8
1
Order By: Relevance
“…In this study, the prevalence of overall ADs and/or BDs was estimated to be 15.7% and 15.2% in the CRS and emmetropia pilots, respectively. This study obtained a lower prevalence of ADs and/or BDs than those reported in three studies [16,25,26] employing adult population. Lara et al [25] examined a sample of 265 symptomatic participants who consecutively attended an optometric clinic and found that 59 (22.3%) presented some type of AD or BD.…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, the prevalence of overall ADs and/or BDs was estimated to be 15.7% and 15.2% in the CRS and emmetropia pilots, respectively. This study obtained a lower prevalence of ADs and/or BDs than those reported in three studies [16,25,26] employing adult population. Lara et al [25] examined a sample of 265 symptomatic participants who consecutively attended an optometric clinic and found that 59 (22.3%) presented some type of AD or BD.…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, the prevalence of overall ADs and/or BDs was estimated to be 15.7% and 15.2% in the CRS and emmetropia pilots, respectively. As shown in Table 5, this study obtained a lower prevalence of ADs and/or BDs than those reported in three studies [16,25,26] employing adult population. Lara et al [25] examined a sample of 265 symptomatic participants who consecutively attended an optometric clinic and found that 59 (22.3%) presented some type of AD or BD.…”
Section: Discussioncontrasting
confidence: 45%
“…Lara et al [25] examined a sample of 265 symptomatic participants who consecutively attended an optometric clinic and found that 59 (22.3%) presented some type of AD or BD. Martin et al [26] examined the prevalence of ADs and/or BDs in a clinical population of 415 Chinese participants, nding that 178 patients (42.9%) in the total sample had general binocular disorders. The samples from both studies were taken from a clinical population seeking solutions to visual symptoms, which might have contributed to the higher prevalence of visual anomalies than the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that convergence insu ciency and divergence insu ciency were associated with refractive error groupings. Convergence insu ciency was more likely to occur in patients with a lower degree of myopia, while divergence insu ciency was more likely to occur in patients with a higher degree of myopia [7]. Another clinical study revealed that high school children (aged between 13 and 18 years) with refractive errors, accommodative or vergence anomalies were more likely to have reduced mean stereoacuity than cases without such anomalies [8].…”
Section: Introductionmentioning
confidence: 99%